2013
DOI: 10.17925/eor.2013.07.01.31
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Surface Morbidities in Glaucoma

Abstract: Introduction: ocular surface disease (oSd) is a major cause of ophthalmological consultation. Within this group, glaucoma patients constitute an important percentage due to the nature of their chronic topical treatment. advances in the understanding of ocular surface pathology on both a cellular and molecular level, and the interaction to the toxic nature of some topical medication solution compounds, are stimulating the development of better alternatives in topical treatment. Materials and Methods: Extensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…It is not uncommon to see clinical manifestations of DED in patients chronically treated with IOP-lowering eye drops. It has been shown in some studies that 66% of patients with severe DED also have glaucoma, 8 and around 60% of patients with glaucoma receiving topical therapy report DED symptoms 9,10 that appear at the initiation of medical treatment. 11 These side effects may be triggered by the active compound, by the preservatives included in the formulation, or both.…”
Section: Introductionmentioning
confidence: 99%
“…It is not uncommon to see clinical manifestations of DED in patients chronically treated with IOP-lowering eye drops. It has been shown in some studies that 66% of patients with severe DED also have glaucoma, 8 and around 60% of patients with glaucoma receiving topical therapy report DED symptoms 9,10 that appear at the initiation of medical treatment. 11 These side effects may be triggered by the active compound, by the preservatives included in the formulation, or both.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the mean count of goblet cells showed significant reduction by the end 12 month of study period, almost in all patients. The prevalence of OSD among users of preserved topical antiglaucoma medications was significantly higher than among nonusers as assessed by FTBUT (83.5% vs. 57.3%; P<0.001), Schirmer I (30.1% vs. 17.5%; P = 0.033), and ocular surface staining (62.1% vs. 31.1%; P<0.001) [1] .…”
Section: Discussionmentioning
confidence: 85%
“…Ocular surface disease (OSD) is a major cause of ophthalmological consultation [1] . Within this group, glaucoma patients constitute an important percentage due to the nature of their chronic topical treatment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations